ELEMEN MESIN DALAM KARYA FOTOGRAFI STILL LIFE - Robertus Ardy Kusumo (Saraswati)
Machine has become a commodity for humans, and human proximity to the engine can no longer be denied and the implications for development of the era as well. Birth of machine initially used as a proponent of human life. Development of the era can be seen from the machines that have been produced by humans, from the standpoint of that we can see how the pattern of human life by looking at a machine that has both machines they created as a tool or machine work as a complementary tool. Deconstruction method used in the creation of this work, deconstruction which was originally developed from the standpoint of language, then it turns out is also relevant to the fields of art. Deconstruction in the creation of this work is an act subject to dismantle an object that is composed of various elements, or elements that deserved dismantled but not destructive. Non-destructive, which means unpacking to be rebuilt according to the original capacity, but to form a new meaning. The creation of this work would like to pass on the role of photography is essentially just as conventional documentation tool and a representative will be the ideal tool when the author can see the pattern of how much influence the times resulting from the creation of the machines as a human helper.Key words: deconstruction, elements, expression photo, machine, still life